2019
DOI: 10.3390/ijms20102425
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Lipid Mediators in Acute Myeloid Leukemia

Abstract: In spite of therapeutic improvements in the treatment of different hematologic malignancies, the prognosis of acute myeloid leukemia (AML) treated solely with conventional induction and consolidation chemotherapy remains poor, especially in association with high risk chromosomal or molecular aberrations. Recent discoveries describe the complex interaction of immune effector cells, as well as the role of the bone marrow microenvironment in the development, maintenance and progression of AML. Lipids, and in part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 119 publications
(132 reference statements)
1
18
0
Order By: Relevance
“…Besides directly mediating inflammation, PGE 2 might be used as an intermediate not only in the signaling between immune cells but also between immunity and tumors. Hence, PGE 2 released from DCs affects the generation and proliferation of Tregs by immunosuppressive cytokines like IL-10, whereas PGE 2 released from tumor cells is able to regulate DC maturation [ 37 , 38 , 39 ]. This COX2/PGE 2 pathway is also involved in the regulation of the immune checkpoint enzyme expression, like PD-L1, in tumor-infiltrating macrophages and other myeloid cells [ 40 ].…”
Section: Lipid Metabolism Impacts Immune Activation Against Tumor mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides directly mediating inflammation, PGE 2 might be used as an intermediate not only in the signaling between immune cells but also between immunity and tumors. Hence, PGE 2 released from DCs affects the generation and proliferation of Tregs by immunosuppressive cytokines like IL-10, whereas PGE 2 released from tumor cells is able to regulate DC maturation [ 37 , 38 , 39 ]. This COX2/PGE 2 pathway is also involved in the regulation of the immune checkpoint enzyme expression, like PD-L1, in tumor-infiltrating macrophages and other myeloid cells [ 40 ].…”
Section: Lipid Metabolism Impacts Immune Activation Against Tumor mentioning
confidence: 99%
“…This makes fatty acids robust biomarker candidates. Recent studies have shown that genetic alterations observed in acute myeloid leukemia (AML) patients control lipid dynamics and metabolism [ 39 , 85 ]. Interestingly, patients with AML can be identified by specific lipid signatures in plasma [ 86 ] and bone marrow [ 87 ].…”
Section: Lipids As Biomarkers Of Immune Response To Cancermentioning
confidence: 99%
“…Lipids, which have historically been considered as mere structural components of cell membranes, are now widely considered as key nutrients and signal transducers that play a major role in oncogenic pathways (Hannun and Obeid, 2018;Loew et al, 2019;Wang et al, 2018).…”
Section: Targeting Lipid Metabolism For Cancer Therapymentioning
confidence: 99%
“…Public health issues, cancer, and cardiovascular disease are the foci of three of the articles. Two of these reviews address the role of polyunsaturated-derived mediators in hematologic malignancies [13], and the last review is related to the involvement of lipid metabolism modifications in the pathogenesis of viral infection-induced cancers [14]. Solati and colls.…”
Section: Applicationsmentioning
confidence: 99%